Adsorption of Mercury on Oxidized Graphenes - Talia Tene; Stefano Bellucci; Marco Guevara; Fabian Arias Arias; Miguel Ángel Sáez Paguay; John Marcos Quispillo Moyota; Melvin Arias Polanco; Andrea Scarcello; Cristian Vacacela Gomez; Salvatore Straface; Lorenzo S. Caputi; F. Javier Torres (Nanomaterials, 2022)
Graphene oxide (GO) and its reduced form, reduced graphene oxide (rGO), are among the most predominant graphene derivatives because their unique properties make them efficient adsorbent nanomaterials for water treatment. Although extra-functionalized GO and rGO are customarily employed for the removal of pollutants from aqueous solutions, the adsorption of heavy metals on non-extra-functionalized oxidized graphenes has not been thoroughly studied. Herein, the adsorption of mercury(II) (Hg(II)) on eco-friendly-prepared oxidized graphenes is reported. The work covers the preparation of GO and rGO as well as their characterization. In a further stage, the description of the adsorption mechanism is developed in terms of the kinetics, the associated isotherms, and the thermodynamics of the process. The interaction between Hg(II) and different positions of the oxidized graphene surface is explored by DFT calculations. The study outcomes particularly demonstrate that pristine rGO has better adsorbent properties compared to pristine GO and even other extra-functionalized ones.